Applications of single-tree selection guideline following a DBq approach on Nepal’s community forests - Cedamon, E.; Paudel, G.; Basyal, M.; Nuberg, I.; Shrestha, K. K. (Banko Janakari, 2018)
There is growing interest by forest users, government forest officers and policy makers on maximising forest goods and livelihood provisions from community forestry in a sustainable manner. However, the way several mature community forests are currently managed based on selection, e.g. negative thinning and crown thinning, is questionable as it results to decline in forest stock, timber quality and regeneration. To assist forest users in managing their community forests, an action research was implemented in Kavre and Lamjung to manage planted Pine (Pinus spp.) and naturally regenerated Sal (Shorea robusta) through selection system. This paper describes the q-factor and its relevance for sustainable community forest management in Nepal. The simple guideline for selection system introduced to 30 community forest users groups in six sites are presented for wider adoption and policy recommendation. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page: 104-112